PENGARUH PENAMBAHAN ABU JERAMI PADI TERHADAP KUAT TEKAN BETON - Gladtha Z. P. Senduk; Nicky Willem Rampengan; Yessy C. S. Pandeirot (Sustainable Construction (SUSCON), 2024)
Concrete is a very important material in the construction sector. This research was conducted to determine the optimum compressive strength value achieved from a mixture of rice straw ash in various variations of concrete mixtures. In this study, tests were carried out for 16 MPa and 20 MPa concrete mixtures with variations in the addition of 3%, 6% and 9% rice straw ash. Which is taken from the weight of cement. From the results of variations in the addition of rice straw ash, the optimum compressive strength value for the 16 MPa mixture with the RSA-6% variation was 18.31 MPa and for the 20 MPa mixture the value for the RSA-6% variation was 22.57 MPa. For the mixed compressive strength values of 16 MPa, variations of 0%, 3%, 6%, 9% are 19.79 MPa, 17.76 MPa, 18.31 MPa and 17.20 MPa, respectively. And for the compressive strength value of a 20 MPa mixture, variations of 0%, 3%, 6%, 9% are 23.31 MPa, 21.64 MPa, 22.57 MPa, and 21.09, respectively. So it can be concluded that the optimum mixture for adding rice straw ash is obtained at an addition of 6%.